Understanding Material Text Cultures. A Multidisciplinary View - Hilgert, Markus (Ed.) (De Gruyter, 2016)
The present volume comprises 6 highly original studies on material text cultures in different nontypographic societies stretching from the 3rd millennium cuneiform textual record of Ancient Mesopotamia to 20th century Qur$1 (Banic boards of northern and central African provenience. The volume provides a multidisciplinary approach to material text cultures complementary to the interdisciplinary, strongly theory-grounded research scheme of the CRC 933.s
English
Keywords: Material text cultures; nontypographic societies